Rancang Bangun Sistem Informasi Monitoring Dashboard Traffic Work Order Berbasis Web - Giandari Maulani; Handi Komara; Santi Meiliana (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2020)
Information Technology plays an important and dominant role in the business process or the operational management of the company. So with the development of the role of the world of Information and Technology, computer processes are used not only as data processing. but a computer can be a media of information that can be accessed at any time. The application of the Traffic Work Order Dashboard System provides many benefits for companies in order to improve company performance more effectively and efficiently. In carrying out the input is still using office applications in the form of Microsoft Excel and services using paper media to the customer queue, causing service information to the customer to be slow so that performance is not optimal. The service process in the work order information for customers is needed so that the printing service work performed can be seen by customers who are waiting for the results of each order. Then a Web-based Traffic Work Order Dashboard system was built to make it easier for customers. In determining research and design requires a method to see the development of the design carried out in the study, the methods applied include the Waterfall SDLC method which is expected to be able to easily determine the achievement of a system, where a website system that has been designed using PHP Framework Codeigniter as a programming language and SQL as a database storage container. In designing this application system using Unified Modeling Language (UML) as a modeling tool consisting of Use Case Diagrams, Activity Diagrams, and Sequence Diagrams. The results of the web-based Traffic Work Order Dashboard system are expected to provide solutions to the problems encountered.